Eddie and his big deals - Haywood, Carolyn, 1898- (New York : Beech Tree Books, 1990)
Eddie can't stand it when the new boy next door turns out to be a girl--a girl who's an even more determined collector of "valuable properties" and other assorted junk than he is.
Keywords: Friendship -- Fiction